The Effect of English Songs on Pronunciation Skills of Vocational High School Students - Leni Yuniati; Ahmad Syafiq; Dyah Sih Pratiwi (Journal of English Education, Literature and Linguistics, 2025)
Abstract One of the goals of this research is to find out whether pupils' pronunciation improves after listening to English songs taught at a vocational school in Bandar Lampung. Two cycles of three sessions each were used to conduct the study using a Classroom Action Research (CAR) design. In the 2023–2024 school year, thirty tenth graders served as the subjects. Assessments of pronunciation, classroom observations, and reflective notes were utilized to gather data. As a consequence of using Ed Sheeran's "Perfect" during practice in Cycle I, 60% of students were able to reach the minimum score requirement of 75 or above. The second cycle saw an increase of 83% thanks to Adele's Someone Like You. Students' motivation, engagement, and confidence in pronouncing English words all improved, according to the qualitative findings of this study. In conclusion, songs are a great way to make class more fun and interactive while also improving students' pronunciation abilities. Keywords: English Songs, Classroom Action Research, Pronunciation